Rooted in place: Regional innovation, assets, and the politics of electric vehicle leadership in California, Norway, and Québec. (May 2022) - Lemphers, Nathan; Bernstein, Steven; Hoffmann, Matthew; Wolfe, David A.
Abstract: In the media, Norway, California, and Québec are widely acknowledged as innovative leaders in transportation electrification. Yet, what does leadership mean and how did these jurisdictions achieve it? We contend that leadership reflects both intentional forethought through early, experimental and innovative policy to promote electric vehicles and the on-the-ground successful outcomes of these policies. All three jurisdictions have embarked on different leadership paths. We argue that these differences are a function of how electromobility policy entrepreneurs engaged unique pre-existing local assets and activated similar political mechanisms of normalization, coalition building and capacity building. When policy actors harness mutually reinforcing political and industrial dynamics, electric vehicle policies can scale up. Eventually, these dynamics may lead to new industrial path development and the decarbonization of the transportation sector. Highlights: California, Norway, and Québec have emerged as leaders in electric vehicle policy. Unique pre-existing local political, economic and natural assets are key factors. Mutually reinforcing political and industrial dynamics facilitate scaling. Scaling may lead to new industrial paths and transportation decarbonization.